Etiology and Symptoms of Epilepsy from the Perspective of Traditional Persian Medicine Scientists - Haleh Tajadini; Elham Akhtari; Rostam Seifadini; Mahdiyeh Khazanehha (Tehran University of Medical Sciences, 2018)
Epilepsy is a relatively common neurological disease classified as a chronic disease in modern medicine. Different treatments have been suggested for this disease, but they have failed in complete treatment of some types of epilepsy. Since Traditional Persian Medicine is one of the medical schools with special perspectives on epilepsy, we aimed to review the etiology and symptoms of epilepsy from the perspective of Dr. Ahmadieh, the contemporary physician, and some well-known traditional medicine practitioners [hakims] in order to obtain a new pattern in recognition and classification of epilepsy. Valid texts of traditional medicine in different historical periods including: The Canon of Medicine (Avicenna, 980-1037AD), Sharhe Asbab va Alamat (Nafis ibn Avaz Kermani), Zakhireye Kharazmshahi (Jorjani), Exire Aazam (Nazem Jahan), Moalejate Aghili (Aghili Alavai Khorasani Shirazi), Kholasat al-Hekma (Aghili Alavai Khorasani Shirazi), Tebe Akbari (Shah Arzani Dehlavi) and Mizan Al-Teb (Hakim Arzani) with focus on opinions of Dr. Ahmadieh (Abdollah Ahmadieh), were investigated. Relevant issues to epilepsy and its etiology and symptoms were reviewed and the common points and differences of various perspectives were gathered. According to traditional practitioners, epilepsy is a partial obstruction occurred in brain paths and ventricles preventing organs to perform their natural function. Familiarity with perspectives of traditional medicine from etiology and symptoms of epilepsy would help to suggest a new and practical classification of the disease. Thus, it seems that attention to these perspectives could provide a new approach for prevention, diagnosis and treatment of epilepsy.